The method of time analysis of a carving turn and its phases - Vodickova, S.; Vaverka, F. (Science and Skiing IV, 2008)
INTRODUCTION: One of the continuously discussed problems in alpine skiing is the turn decomposition into single phases (Müller et al., 1998; Raschner et al., 2001, and others). When decomposing the turn, authors mostly use kinematic or dynamic analysis, but exact expression of the time duration of the phases has not been defined. This paper presents a method that allows total time duration of the turn and its initiation and steering phases definition, based on dynamometric reaction force record.